Pensées. - Pascal, Blaise, 1623-1662 (Open Road Integrated Media, Inc., 2016)
An illuminating exploration of the nature of faith from one of history's greatest thinkers Blaise Pascal was not a gambler, but he posited one of the most famous wagers of all time: Every man's life is a bet against God. It is a wager that any man can win, however. Sacrifice earthly pleasures--drink, lust, sin, etc.--and a lifetime of happiness awaits, in this world or the next. Live every day as if God exists, and you can't lose. Pascal devised his wager in the seventeenth century, but the lessons written by this brilliant man ring true today. In this collection of fragments intended as a defense of Christianity, everything is up for debate. From the nature of love to the relationship between scientific inquiry and religious faith, Pascal shows that skepticism and devotion go hand in hand.